Development of Fable Picture Storybooks as a Learning Medium to Promote Anti-Bullying in Early Elementary Education - Ulfah, Amaliyah; Saraswati, Putri Andhina; Adityas, M. Tolkhah (Jurnal Pendidikan Progresif, 2025)
Development of Fable Picture Storybooks as a Learning Medium to Promote Anti-Bullying in Early Elementary Education Objectives: This study aims to develop a picture storybook that is valid, practical, and effective as an anti-bullying learning medium for elementary school students. Methods: The research employed a development approach (Research and Development) using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants in this study were first-grade students from SD N Giwangan and SD Muhammadiyah Sambisari. Data were collected through questionnaires, interviews, and observations. Findings: The developed anti-bullying fable picture storybook was evaluated by experts and received high feasibility ratings: 92.5% from media experts (very feasible), 96% from content experts (very feasible), and 83% from instructional experts (feasible). Additionally, teacher assessments yielded an average score of 49 out of a possible 50, with a feasibility percentage of 98% (very feasible). A significant improvement in students' understanding of bullying including its definition, forms, and consequences was observed after using the storybook. This is supported by an increase in the average pre-test score (M = 65.20) to the post-test score (M = 82.75). Conclusion: The anti-bullying picture storybook developed in this study is an effective educational tool and holds strong potential for integration into bullying prevention efforts in elementary schools. It offers an engaging and interactive alternative learning resource that supports schools in fostering a safer and more supportive learning environment for all students. Keywords: picture strorybook, learning media, anti-bullying, elementary school.